Moisture absorption membrane and hydrofluoric acid removal membrane containing aramid nanofibers
A rapid preparation method for aramid nano fiber membranes using aramide microfiber and DMSO/KOH effectively addresses moisture and HF issues in lithium-ion batteries, enhancing battery performance and safety.
Patent Information
- Application Number
- JP2022560331
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-03
- Filing Date
- 2021-04-02
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2041-04-02
AI Technical Summary
Existing methods for preparing aramid nano fiber membranes are time-consuming and inefficient, and they do not effectively address the issue of moisture and hydrogen fluoride (HF) in lithium-ion batteries, leading to battery degradation and dendrite growth.
A rapid preparation method involving a mixture of aramide microfiber and aramid nano fiber with dimethyl sulfoxide (DMSO) and potassium hydroxide, followed by high-shear mixing, negative pressure, and drying, to create a nano porous separator film that absorbs moisture and removes HF, indicated by color change.
The method significantly reduces moisture and HF in lithium-ion batteries, extending battery life and preventing dendrite growth, with the film showing high ionic conductivity and moisture absorption capacity, and providing a visual HF exposure indicator.
Smart Images

Figure 0007624239000003 
Figure 0007624239000004 
Figure 0007624239000005
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to pending U.S. Provisional Patent Application No. 63 / 004,631, filed April 3, 2020, which is incorporated by reference in its entirety. FIELD OF THE DISCLOSURE The present invention relates to a moisture absorbing membrane comprising a mixture of aramid microfibers and aramid nanofibers capable of absorbing liquid equivalent to at least 1% of the GSM of the membrane, a rapid method for producing such membranes, the use of such membranes in batteries, a rapid method for preparing nanoporous separator membranes comprising aramid microfibers and aramid nanofibers, a hydrogen fluoride (HF) removal membrane, a method for reducing humidity in a battery, a method for reducing free HF in a battery, and a visual indicator of HF exposure. [Background technology]
[0002] Kevlar with various diameters over several hundred nanometers TM The formation of aramid-related fibers and super-strong fibers has been used to produce membranes. See Zhang (2010) Applied Surface Science 256:2104-2109, Daido et al. US Patent No. 6,291,106, and Zhang et al. (2013) Solid State Ionics 245-246:49-55. Additionally, membranes and films containing aramid nanofibers are known in the art. However, the methods of preparing aramid nanofiber films or aramid nanofiber membranes are time-consuming, often requiring several weeks.
[0003] The preparation of ANF-based ICM and separator composites with the nanometer-scale porosity required for ionic conduction and dendrite suppression can be achieved following a layer-by-layer (LBL or LbL) technique. See Yang et al. (2011) ACS Nano 5:6945-6954. LBL-produced materials also exhibit unparalleled uniformity required for the elimination of nanoscale "weak spots" that facilitate dendrite growth. See Shim et al. (2010) ACS Nano 4:3725-3734; Shim et al. (2009) ACS Nano 3:1711-1722; Krogman et al. (2007) Langmuir ACS J Surfaces Colloids 23:3137-3141; Jiang et al. (2006) Advanced Materials 18:829-840. The ability of the technique to build up micrometer-thick composite layers with high ionic content results in high ionic conductance. However, LBL is based on the deposition of a single nanometer-scale layer at a time, and as a result requires non-traditional manufacturing equipment and can be slow to implement. It is not trivial that other methods utilizing ANFs can provide similar performance across multiple parameters required for ICMs and separators, including but not limited to stiffness, strength, pore size and distribution, ionic conductance, thermal resilience, and thickness variation.
[0004] Another major obstacle to the cost-effective deployment of advanced lithium-ion batteries (LIBs) is the issue of capacity fading / cycle life degradation. Conventional lithium-ion battery electrolytes typically consist of a mixture of linear and cyclic organic carbonates and lithium hexafluorophosphate (LiPF6). Even the purest battery electrolytes typically contain about 25 ppm water, which is not mechanism limited due to the hydroscopic nature of LiPF6. The presence of water and moisture causes the decomposition of HF and subsequent formation of HF, which attacks and dissolves the transition metals in many different cathode compositions. The presence of hydrofluoric acid (HF) in the liquid electrolyte has been identified as the primary cause of this decomposition and battery life degradation. The dissolved metal ions migrate to and plate the lithium / graphite anode, causing it to fail. HF can also attack and leach out inorganic species (e.g., LiF) deposited on the cathode surface. When this occurs, the cathode surface where LiF was once deposited is exposed to the electrolyte solution, and further electrolyte decomposition occurs on the newly exposed surface. Several approaches have been used to improve the structural stability of the cathode in the presence of HF, including protective coatings and the use of basic additives in the electrolyte that chemically scavenge the HF. Protective / reactive coatings have also been deposited on the separator. One drawback to all of these approaches is that they add mass and volume to the LIB without contributing to its capacity and / or power density. Also, battery decomposition is not easily detectable prior to the battery's failure point. It is difficult to know when the battery has started to degrade. Summary of the Invention
[0005] The present embodiment provides a method for the rapid preparation of nanoporous separator membranes comprising aramid microfibers and aramid nanofibers, comprising the steps of: preparing a mixture of aramid pulp, dimethyl sulfoxide (DMSO) and potassium hydroxide; exposing the mixture to high shear forces to form a slurry; preparing a mold with a layer of DMSO; adding the slurry to the mold; stirring the slurry and DMSO; applying negative pressure to the slurry in the mold; removing residual DMSO; and drying the slurry to form a nanoporous separator membrane comprising aramid microfibers and aramid nanofibers. In one embodiment, the ratio of aramid microfibers to aramid nanofibers is in the range of 90:10, 80:20, 70:30, 50:50, 30:70, 20:80 to 10:90. In one embodiment of the method, the aramid microfibers and aramid nanofibers are 0.1-2% of the slurry. In one embodiment, the method forms a nanoporous separator membrane in less than 24 hours, less than 10 hours, less than 8 hours, less than 5 hours, or less than 3 hours. In one embodiment, the step of exposing the formulation to high shear occurs for less than 2 hours, less than 1 hour, less than 30 minutes, less than 15 minutes, less than 10 minutes, or less than 5 minutes. In one embodiment, the negative pressure is applied at about 7-12 Hg. In one embodiment of the method, at least 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or 95% of the DMSO is removed from the slurry by the negative pressure. In one embodiment, the negative pressure is applied for less than 5 minutes, less than 2 minutes, less than 1 minute, less than 50 seconds, less than 45 seconds, less than 40 seconds, less than 35 seconds, or less than 30 seconds. In one embodiment of the method, residual DMSO is removed with water. In one embodiment of the method, drying is performed at elevated temperature. The elevated temperature can be in the range of 50-100° C., 60-90° C., 65-80° C., or 65-75° C. In various embodiments of the method, the mold is selected from the group of molds consisting of sheet molds, casting molds, mold and deckle, and cylinder molds.
[0006] In one embodiment, the present application provides a hydrogen fluoride (HF) rejection membrane comprising aramid microfibers and aramid nanofibers, where binding of HF to the separator membrane causes the separator to discolor.
[0007] In one embodiment, the present application provides a hygroscopic membrane comprising aramid microfibers and aramid nanofibers, wherein the membrane is capable of absorbing a liquid equivalent to at least 1% of the membrane mass. In one aspect, the nanofibers are produced by exposing aramid microfibers to a base in an aprotic solvent. In various aspects, the base is selected from the group of bases consisting of Group I bases, Group II bases, sodium hydroxide, potassium hydroxide, lithium hydroxide, barium hydroxide, and magnesium hydroxide. In one aspect, the hygroscopic membrane further comprises at least one additive. The additive can be selected from the group including Al2O3. In one aspect of the membrane, the tensile strength of the membrane reduces dendrite growth. In one aspect, the tensile strength of the membrane is at least 35 MPa. In one aspect, the membrane exhibits an air permeability of greater than 65 Gurley seconds. In one aspect, the membrane exhibits high ionic conductivity as measured by the McMullin number, which is the ratio of the resistance of the electrolyte-filled separator to the resistance of the electrolyte alone. A McMullin number of less than 15, less than 12, less than 10, or less than 8 indicates high ionic conductivity. In other embodiments, the membrane has an average pore size d dendr In one embodiment of the membrane, the membrane can absorb liquid equivalent to at least 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, or more of the membrane mass.
[0008] The present application further provides a battery having increased moisture removal properties comprising the hygroscopic membrane of the present application. In some embodiments, the battery exhibits reduced HF damage. In various embodiments, a component of the battery is lined with a hygroscopic material. The component may be selected from the group of components including an anode, a cathode, and an encapsulant. In one embodiment, the battery includes a nanoporous separator membrane comprising the hygroscopic membrane. In one embodiment, the battery exhibits at least 90% capacity after 250 cycles.
[0009] The present application provides a method for rapid preparation of a wicking film, comprising the steps of preparing a mixture of aramid pulp, an aprotic solvent, and a base, exposing the mixture to high shear to form a slurry containing aramid microfibers and aramid nanofibers, preparing a mold with a layer of aprotic solvent, applying negative pressure, and drying at elevated temperature to form a wicking film containing aramid microfibers and aramid nanofibers. In one embodiment, the base is selected from the group including Group I bases, Group II bases, potassium hydroxide, sodium hydroxide, lithium hydroxide, barium hydroxide, magnesium hydroxide, and calcium hydroxide. In various embodiments, the Group II bases are selected from the group including barium hydroxide and calcium hydroxide. In one embodiment, the wicking film is prepared in less than 96 hours, less than 48 hours, less than 24 hours, less than 12 hours, less than 6 hours, or less than 3 hours. In one embodiment, the aprotic solvent is DMSO. In various embodiments, the elevated temperature is in the range of 50° C. to 200° C., 60° C. to 190° C., 75° C. to 180° C., 85° C. to 160° C., or 100° C. to 160° C. In one embodiment, the elevated temperature is 180° C. or higher.
[0010] The present application provides a method for reducing water in a battery, comprising incorporating into the battery a moisture wicking membrane of the present application.The present application provides a method for reducing free HF in a battery, comprising incorporating into the battery a moisture wicking membrane as described elsewhere herein.
[0011] The present application provides a visual indicator of HF exposure that includes a wicking membrane and an observation opening in which the wicking membrane is disposed, the wicking membrane changing color upon binding of HF. In one aspect, the present application provides a battery system including the visual indicator of HF exposure. (Incorporated by reference)
[0012] All publications, patents, and patent applications mentioned in this specification are herein incorporated by reference in their entirety to the same extent as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference. [Brief description of the drawings]
[0013] [Figure 1] 1A and 1B show micrographs of scanning electron microscope images of aramid nanofibers obtained from DuPont Kevlar pulp type 979A at magnifications of (FIG. 1A) 25,000× and (FIG. 1B) 2,500×. [Diagram 2] Figure 1 shows the XPS spectral analysis of pure ANF separator. Panel A shows only the carbon (C), nitrogen (N) and oxygen (O) peaks. Panel B shows a zoomed in view of the corresponding carbon region, where the C-C, C-N and C=O bond peaks are clearly visible. [Diagram 3] 3, 3A and 3B are graphs showing the corresponding XPS spectra of a similar ICM that was immersed overnight in 1.2M LiPF6 EC / EMC electrolyte. [Figure 4] 4A and 4B show photographs of an aramid nanofiber membrane (panel A) and an aramid nanofiber membrane immersed in a 1.2 M LiPF6 EC / EMC electrolyte solution containing 10.75 ppm HF (panel B). [Figure 5A] FIG. 5A (panel A) shows a plot of tensile strength (y-axis) versus pKb (x-axis) for hygroscopic films prepared with various bases. [Figure 5B] FIG. 5B (panel B) shows a plot of membrane air permeability, measured in Gurley (seconds), versus pKb (x-axis) for hygroscopic membranes prepared with various bases. [Figure 6] 1 is a graph summarizing data obtained from batteries containing hygroscopic membranes prepared with various bases, with indicated cycle number (x-axis) versus battery capacity % (y-axis). [Figure 7] 1 is a graph summarizing moisture sorption data obtained from moisture sorption films prepared with the indicated bases. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS AND DRAWINGS Unless otherwise defined, all technical and scientific terms used herein have the meaning commonly understood by one of ordinary skill in the art to which this invention belongs.
[0015] As used herein, "A," "an," and "the" can include plural referents unless expressly and unambiguously limited to one referent.
[0016] Provided are a rapid method for preparing nanoporous separator membranes comprising aramid microfibers and aramid nanofibers, an HF-removing membrane, a moisture-wicking membrane capable of absorbing a liquid equivalent to at least 1% of the membrane mass, and a rapid method for preparing the moisture-wicking membrane.
[0017] The term "membrane" is intended to include films, sheets, laminates, fabrics, or planar flexible solids. Membrane properties include, but are not limited to, thickness, strength, flexibility, tensile strength, porosity, and other properties. It is recognized that different membranes or different types of membranes may exhibit different or similar properties.
[0018] Nanoporous separator membranes are known in the art. Nanoporous membranes encompass a wide range of inorganic, organic or composite materials. A wide variety of nanoporous materials have been developed for liquid phase separation. Porous materials are often differentiated based on pore size, size distribution, shape and order. Nanoporous materials have pore sizes that allow small materials to pass through the membrane. In various embodiments, the pore size allows materials smaller than 2 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, 320 nm, 340 nm, 360 nm, 380 nm, 400 nm, 420 nm, 440 nm, 460 nm, 480 nm, or 500 nm to pass through the membrane. Nanoporous separator membranes resist or prevent molecules larger than nano-sized from passing through the membrane.
[0019] The term "ion-conducting membrane" or "ICM" is intended to refer to a separator between two electrodes, be it an anode and a cathode, or a positive electrode and a negative electrode. The ion-conducting membrane divides, separates, or partitions the two regions while allowing the flow of ions between the two regions.
[0020] The term "hygroscopic membrane" is intended to include membranes that can absorb, take up, retain, permeate, internalize, or trap liquid. Liquids of interest include, but are not limited to, organic solutions, aqueous solutions, electrolyte solutions, hydrofluoric acid, HF, and carbonate-based electrolyte solutions. Hygroscopicity is usually described as mass absorbed per amount (mass) of membrane, or as hygroscopic capacity (g liquid / g sample). The hygroscopic membranes of the present application can absorb liquid equivalent to at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or more of the membrane mass. It is recognized that bibulous membranes may generally retain their original dimensions upon absorption of moisture or may generally change their original dimensions by up to 0.5%, 1%, 5%, 10%, 15%, 20%, 35%, 40%, 50%, 60%, 70%, 80%, 90%, 100% or more, and it is also recognized that dimensional changes may occur upon absorption of a threshold level of liquid.
[0021] Aramid fibers are known in the art. Aramid polymers are defined as those that contain aromatic groups and amide linkages in the backbone. Typically, the amide groups provide the linkage between adjacent aromatic groups. In one embodiment, the aramid polymers are characterized as those in which at least 85% of the amide groups in the backbone are directly bonded to two aromatic groups, particularly where the aromatic groups are phenyl groups.
[0022] Aramid fibers include, but are not limited to, para-aramid fibers, meta-aramid fibers, and copolyimide fibers. Para-aramid fiber backbones consist of phenyl groups separated by amide bonds, where the amides link the phenyl groups in a para configuration. Para-aramid fibers are known in the art and include Kevlar, Twaron, TMExamples of suitable poly(para-phenylene terephthalamide) include, but are not limited to, poly(para-phenylene terephthalamide), and PPTA. In a simple form, PPTA can be understood as the reaction product of para-phenylenediamine and terephthaloyl dichloride, although the synthesis is not limited to reacting specific monomers. Meta-aramid can be understood as the product of para-phenylenediamine and isophthaloyl dichloride. Meta-aramid fibers are known in the art and are available from Nomex. TM Copolyamide fibers include, but are not limited to, structures resulting from the polymerization of other aromatic diamines with terephthaloyl chloride or isophthaloyl chloride, or in the presence of para-phenylenediamine. The aramid materials used in the methods and compositions can also be obtained from used bulletproof vests, tents, ropes, or other articles containing Kevlar / aramid macroscale fibers, or from waste or scrap from the manufacture of aramid materials.
[0023] Aramid microfibers are characterized by diameters in the micrometer range. The diameters of aramid microfibers can be in the range of 1μ to 500μ, 1μ to 400μ, 1μ to 300μ, 1μ to 200μ, 2μ to 150μ, 3μ to 140μ, 4μ to 130μ, 5μ to 120μ, 6μ to 110μ, 7μ to 110μ, 8μ to 110μ, 9μ to 110μ, 10μ to 110μ, 20μ to 110μ, 30μ to 110μ, 40μ to 100μ, and 50μ to 90μ. In general, aramid microfibers are characterized by a high aspect ratio, which means that the length of the microfiber is at least 5 times, at least 10 times, or at least 20 times the diameter of the microfiber. It is recognized that aramid microfibers and aramid nanofibers may include branching.
[0024] By aramid nanofiber (ANF) is meant that the diameter of the aramid fiber is in the nanometer range, particularly in the range of 3-100 nanometers, 3-50 nanometers, 4-40 nanometers, 3-30 nanometers, and 3-20 nanometers. In addition to the nanometer range diameter, ANFs are characterized by a high aspect ratio, which means that the length of the fiber is at least 5 times, at least 10 times, or at least 20 times the diameter. In various embodiments, the length of the ANF is greater than 0.1 microns, or greater than 1 micron. Without being limited by mechanism, aramid nanofibers can be produced by exposing aramid microfibers to a base in an aprotic solvent.
[0025] Such aramid membranes are disclosed herein, but may be provided with only such aramid components. Alternatively, other synthetic fibers having the same or similar microfiber and nanofiber diameters may be provided within such membranes to provide other potential properties. Thus, aramid fibers may supplement various types of polymer fibers within the membrane structure, including, but not limited to, cellulose, polyacrylonitrile, polyolefins, polyolefin copolymers, polyamides, polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polysulfone, polyvinyl fluoride, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polymethylpentene, polyphenylene sulfide, polyacetyl, polyurethane, aromatic polyamides, semi-aromatic polyamides, polypropylene terephthalate, polymethyl methacrylate, polystyrene, synthetic cellulosic polymers, and blends, mixtures, and copolymers thereof. Such fibers may be provided as microfibers and nanofibers to form a monolayer structure (nonwoven) with the required aramid fibers present therein. Such structures may be formed according to the materials and methods disclosed, for example, in U.S. Patents 8,936,878, 9,637,861, and 9,666,848. The aramid nanofibers thus contribute to the moisture wicking and HF removal capabilities of such composite polymer fiber structures.
[0026] The ratio of aramid microfibers to aramid nanofibers in the membrane can be in the range of 95:5, 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, 30:70, 20:80, 10:90, or 5:95. In some embodiments, a higher nanofiber ratio is preferred.
[0027] Aramid pulp is a dry processed material made from short, less fibrillated aramid fibers. Aramid pulp is commercially available and any aramid pulp can be used in the process.
[0028] Aprotic solvents are known in the art and include, but are not limited to, dimethylsulfoxide (DMSO) and N-methylpyrrolidone (NMP).
[0029] The bases used in the method include, but are not limited to, Group I and Group II bases, such as sodium hydroxide, potassium hydroxide (KOH), lithium hydroxide, calcium hydroxide, barium hydroxide, and magnesium hydroxide. In some methods, the preferred base is KOH. In other methods, the preferred base is a Group II base. Surprisingly, the hygroscopic membranes differ in their liquid absorption capacity depending on the base from which the hygroscopic membranes are prepared. Preferred bases for preparing the hygroscopic membranes include, but are not limited to, Class II bases. Particularly preferred bases for preparing the hygroscopic membranes include barium hydroxide and calcium hydroxide.
[0030] The rapid method for preparing nanoporous separator membranes includes preparing a blend of aramid pulp, dimethyl sulfoxide, and potassium hydroxide. In general, the aramid pulp and aprotic solvent are blended in the range of 1000 ml solvent per 2.5 g pulp, 750 ml solvent per 2.5 g pulp, 500 ml solvent per 2.5 g pulp, 500 ml solvent per 2.5 g pulp, and 125 ml solvent per 2.5 g pulp, with a range of 250 mL solvent per 2.5 g pulp being preferred. It is further recognized that additional aprotic solvent may be added to the blend to further dilute the solvent to pulp ratio. The ratio of aramid pulp, dimethyl sulfoxide, and potassium hydroxide suitable for preparing aramid nanofiber membranes is known in the art. See, for example, U.S. Patent No. 10,160,833, U.S. Patent Application No. 13 / 120,301, and U.S. Patent Application No. 16 / 067,498. The pulp to KOH ratio can range from 1:2 to 1:100, 1:4 to 1:50, 1:6 to 1:25, and preferably from 1:8 to 1:12.
[0031] The rapid preparation method of the moisture wicking membrane includes preparing a blend of aramid pulp, aprotic solvent, and base. Typically, the aramid pulp and aprotic solvent are blended in the range of 1000 ml solvent per 2.5 g pulp, 750 ml solvent per 2.5 g pulp, 500 ml solvent per 2.5 g pulp, 500 ml solvent per 2.5 g pulp, and 125 ml solvent per 2.5 g pulp, with a range of 250 mL solvent per 2.5 g pulp being preferred. It is further recognized that additional aprotic solvent may be added to the blend to further dilute the solvent to pulp ratio. The base may be selected from a group of bases including Group I bases, Group II bases, sodium hydroxide, potassium hydroxide, lithium hydroxide, barium hydroxide, calcium hydroxide, and magnesium hydroxide. In some embodiments, a Group II base selected from the group including barium hydroxide and calcium hydroxide is used. Surprisingly, by varying the base, moisture wicking membranes with different water absorption capacities are obtained. In general, the amount of base pairing solvent can range from approximately 10 mg base / L solvent, 0.5 mg base / L solvent, 1 mg base / L solvent, 10 mg base / L solvent, 100 mg base / L solvent, 200 mg base / L solvent, 300 mg base / L solvent, 400 mg base / L solvent, 500 mg base / L solvent, 600 mg base / L solvent, 700 mg base / L solvent, 800 mg base / L solvent, 900 mg base / L solvent, 1000 mg base / L solvent, 1.1 g base / L solvent, 1.2 g base / L solvent, to approximately 1.3 g base / L solvent.
[0032] The method of preparing the membrane includes preparing a blend of aramid pulp, an aprotic solvent, and a base. In some methods, a blend of aramid pulp, DMSO, and KOH is prepared in a vessel. The blend is subjected to high shear to form a slurry. Methods of subjecting the mixture to high shear are known in the art and include, but are not limited to, mixing in a high shear mixer. High shear mixers are high speed devices that homogenize, emulsify, disintegrate, reduce particle size, and disperse many different solid and liquid materials. Without being limited to a particular mechanism, materials are sheared when portions of the material are given different speeds using a rotating impeller or high speed rotor. The speed of the material at the tip of the rotor may be different from the speed at the center, which creates shear. High shear mixers can blend solids and liquids that would not normally be blended. Suitable high shear mixers include, but are not limited to, batch high shear mixers, high shear in-line mixers, ultra high shear in-line mixers, and laboratory high shear mixers.
[0033] The exposure of the formulation to high shear force may be for a duration and may occur for less than 5 hours, less than 4 hours, less than 3 hours, less than 2 hours, less than 1 hour, less than 30 minutes, less than 15 minutes, less than 10 minutes, or less than 5 minutes. The duration of exposure to high shear force may be determined by factors such as, but not limited to, total volume, container shape, container size, initial pulp volume, initial pulp consistency, and base. Methods for determining the appropriate duration of exposure to high shear force are known in the art.
[0034] The aramid fiber suspension or slurry typically ranges from 0.05-25% fiber concentration, 0.1-20% fiber concentration, 0.1-15% fiber concentration, 0.1-10% fiber concentration, 0.1-8% fiber concentration, 0.1-6% fiber concentration, 0.1-4% fiber concentration, and preferably 0.1-2% fiber concentration. It is recognized that the slurry content for making nanofibers may be different from the slurry content for making sheets. It is understood that the fiber slurry for making sheets may be lower or more dilute than the fiber slurry for making nanofibers. In one embodiment, the initial aramid fiber slurry is approximately 1% fiber slurry, while the fiber slurry for making sheets is approximately 0.125%.
[0035] In an aspect of the method, a mold may be prepared with a layer of an aprotic solvent such as DMSO. The slurry may be added to the mold. It is recognized that in some embodiments, it is preferable to add the slurry in a manner that minimizes or reduces turbulence. In other embodiments, the technique used to add the slurry may result in turbulence, bubbles, or air pockets. Molds for forming membranes, sheets, or films are known in the art. Any mold suitable for membrane formation may be used in the method. Suitable molds include, but are not limited to, sheet molds, casting molds, molds and deckles, and cylinder molds.
[0036] A method for the rapid preparation of nanoporous separator membranes or wicking membranes includes agitating a slurry in the presence of an aprotic solvent. Methods for agitating the slurry and aprotic solvent are known in the art and include, but are not limited to, stirring, shaking, vibrating, rolling, and tumbling. In some aspects of the method, additional aprotic solvent is added to the slurry.
[0037] The step of applying negative pressure can be configured in a variety of ways. Methods of applying negative pressure are known in the art. Negative pressure can be applied in the range of about 1-50 Hg, 2-40 Hg, 3-30 Hg, 4-20 Hg, 5-15 Hg, 6-14 Hg, 7-13 Hg, and 7-12 Hg. The negative pressure can remove at least 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, 96%, 97%, 98%, 99% or 100% of the aprotic solvent. Negative pressure can be applied for any desired period of time. Negative pressure may be applied for less than 1 hour, less than 30 minutes, less than 15 minutes, less than 10 minutes, less than 5 minutes, less than 2 minutes, less than 1 minute, less than 55 seconds, less than 50 seconds, less than 45 seconds, less than 40 seconds, less than 35 seconds, or less than 30 seconds.
[0038] The method may include removing residual aprotic solvent, hi some embodiments, the residual aprotic solvent may be removed with water.
[0039] The rapid preparation method of the membrane may include drying the slurry to form a membrane comprising aramid microfibers and aramid nanofibers. Drying methods are known in the art. Drying may occur at an elevated temperature. The elevated temperature for the nanoporous separator membrane may be in the range of 50°C to 100°C, 60°C to 90°C, 65°C to 80°C, or 65°C to 75°C. The elevated temperature for the hygroscopic membrane may be a temperature selected from the group consisting of 50°C, 60°C, 65°C, 70°C, 75°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, and 220°C or higher. The elevated temperature for the hygroscopic film may be in the range of 50°C to 100°C, 60°C to 90°C, 65°C to 80°C, or 65°C to 75°C.
[0040] The rapid preparation methods for membranes including aramid microfibers and aramid nanofibers may yield membranes in less than 24 hours, less than 12 hours, less than 10 hours, less than 8 hours, or less than 3 hours. It is recognized that the rapid preparation methods for nanoporous separator membranes may yield nanoporous separator membranes in a similar or different time frame than the rapid preparation methods for hygroscopic membranes yield hygroscopic membranes.
[0041] Hydrogen fluoride, HF, and the aqueous form of hydrogen fluoride (hydrofluoric acid) are highly corrosive compounds. HF corrosion is a problem especially with batteries containing lithium, lithium hexafluorophosphate, or other lithium salts containing fluorine. The present application provides an HF-removing membrane comprising aramid microfibers and aramid nanofibers. The term "HF-removing membrane" is intended to refer to a membrane that removes, binds, traps, connects, reacts, secures, or confines HF. HF in the HF-removing membrane has less ability to damage components than free HF. In some embodiments, the HF-removing membrane extends battery life. The HF-removing membrane comprising aramid microfibers and aramid nanofibers changes color upon HF binding to the membrane. Before binding with HF, the membrane may exhibit a yellow or yellowish hue. Upon binding with HF, the membrane changes color from its original color to a pink, red, or pinkish hue. The color change is a visual indicator of HF exposure and HF binding of the membrane. The color change indicates that the battery or battery components need replacing.
[0042] The hygroscopic films of the present application may further include one or more additives, including but not limited to Al2O3, which may increase hygroscopicity, increase strength, or change other properties of the hygroscopic film.
[0043] Many of the safety issues in modern batteries are related to dendrite growth and anode expansion under charge. TMDendrite perforation of porous polymer separators such as the 2400 is the most common mechanism of spontaneous battery failure that can lead to short circuits and fires. Dendrite growth also represents a significant obstacle in the development of batteries with lithium metal anodes that can approach the theoretical limits of lithium-based energy storage devices in terms of capacity, power, and weight. Dendrites propagate through the membrane via the path of least mechanical resistance. The dendrite growth area, d dendr The size of the d is 50 to 100 nm. dendr When the ICM has soft pores larger than d, it is the low modulus parts rather than the high stiffness parts that determine the propagation of dendrites. dendr When the average pore size is smaller than d, the dendrite growth area experiences a resistance equal to the average elastic modulus of the membrane. To prevent dendrite formation, many different approaches are used, such as additives to gel and liquid electrolytes, composite gel electrolytes using inorganic fillers, ANF-PEO or ANF-PAO membranes (see, for example, U.S. Application Serial No. 15 / 120,301). The hygroscopic membranes provided herein have an average pore size of d dendr The various hygroscopic films of the present application reduce dendrite growth. By "reducing dendrite growth" we mean a reduction in the rate of dendrite growth, an absolute reduction in dendrite growth, and a reduction in dendrite growth over a particular time frame, as compared to dendrite growth in the absence of the claimed hygroscopic film.
[0044] A hygroscopic membrane is provided that exhibits high ionic conductivity. The term "high ionic conductivity" is intended to relate to an ionic conductivity of greater than 0.01 mS / cm, 0.05 mS / cm, 0.1 mS / cm, 0.5 mS / cm, 1 mS / cm, 5 mS / cm, 10 mS / cm, 15 mS / cm, 20 mS / cm, 25 mS / cm, 30 mS / cm, 35 mS / cm, 40 mS / cm, 45 mS / cm, 50 mS / cm, 55 mS / cm, 60 mS / cm, or 70 mS / cm.
[0045] Batteries are provided that include a hygroscopic membrane and exhibit increased moisture removal properties. The batteries provided may exhibit reduced HF damage. The term "reduced HF damage" is intended to relate to reduced, lowered, and / or improved HF-related damage to one or more battery components, reduced or reduced HF-related damage over a period of time, or extended periods at moderate to high capacity, as compared to a battery that does not have a hygroscopic membrane. The batteries with increased moisture removal properties may include components lined with a hygroscopic membrane that includes aramid microfibers and aramid nanofibers. The components may be selected from a group of components that include an anode, a cathode, an encapsulant, and an ion-conducting membrane. The term "encapsulant" is intended to relate to any structure or device that encloses the anode, cathode, and electrolyte, such as, but not limited to, a wall, lid, top, floor, can, or canister. Batteries with wicking membranes including aramid microfibers and aramid nanofibers can exhibit at least 90% capacity after 100, 150, 200, 250, 300, 350, 400, or more cycles. Batteries with wicking membranes including aramid microfibers and aramid nanofibers can exhibit at least 70% capacity after 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, 500, or more cycles.
[0046] A method for reducing moisture in a battery is provided. The method includes incorporating into the battery a moisture wicking membrane that includes aramid microfibers and aramid nanofibers. A method for reducing free HF in a battery is provided. The method includes incorporating into the battery a moisture wicking membrane that includes aramid microfibers and aramid nanofibers.
[0047] Also provided is a visual indicator of HF exposure comprising a wicking membrane comprising aramid microfibers and aramid nanofibers and an observation opening. The wicking membrane is disposed within the observation opening. The wicking membrane changes color when HF binds to the membrane. The color change is indicative of HF binding and exposure. It is recognized that the color change may be detected by a person or a device. Also provided is a battery system comprising the visual indicator of HF exposure.
[0048] It will be understood that reference to the following examples is for illustrative purposes only and does not limit the scope of the claims. EXAMPLES
[0049] Example 1 Preparation of nanoporous separator (long shape) The process involves extended (1-5 weeks) digestion of aramid pulp, exemplified by but not limited to DuPont Kevlar Pulp Type 979A Merged 1F1710, in dimethylsulfoxide (DMSO) at a specific weight ratio of Kevlar pulp to added KOH, exemplified by but not limited to 1:8-1:12 pulp-KOH mass ratios. ANF prepared using this protocol was processed into sheets of thickness 2-100 microns by filtering, spraying, casting, doctor blading, and painting, followed by rinsing with water and drying.
[0050] The dried ANF-based sheet was separated from the microporous substrate. Suitable microporous substrates include, but are not limited to, Millipore Mitex PTFE membrane filters, Omnipore PTFE membrane filters, Sterlitech PTFE membrane filters, and Sumitomo Electric Poleflon PTFE membrane filters.
[0051] The nanoparticle separator comprising aramid nanofibers produced by the described method has a pore size of 5-150 nm, a tensile strength of 10-200 MPa, and a Gurley number of 30-500.
[0052] Nanoporous separators were incorporated into batteries. The separator from digested ANF exhibits the ability to sense the degradation of the electrolyte used in the battery by changing color from light yellow to pink upon exposure to the degraded electrolyte. Results from one such experiment are shown in Figure 4A and Figure 4B. Note the dark color of the membrane exposed to the 1.2 M LiPF6EC / EMC electrolyte solution in Figure 4B (Figure 4, panel B). The ANF separator exhibits a reddish color upon HF binding.
[0053] Example 2 Rapid preparation process of nanoporous separator membrane
[0054] Kevlar pulp (5 g) was blended with 500 mL of DMSO and 0.5 mL of KOH powder. This mixture was subjected to high shear mixing in a Silverson high shear lab mixer at 6000-8000 rpm for 30 min to 6 h to produce a slurry. Typically, this slurry contained 0.1% to 2% fibre suspension. The colour of the slurry progressed from cream to yellow to orange. In some experiments, the temperature reached 55 °C in the first 30 min. The slurry was diluted by adding 500 mL of DMSO and mixed for 2 min. One litre of DMSO was then added. The diluted mixture was stirred at approximately 700 rpm for at least 2 h.
[0055] A sheet mold with 400 mesh 316 L stainless steel mesh used as the forming wire was prepared with KOH. A thin layer of DMSO was poured onto the surface of the mold. The DMSO layer suspends the aramid nanofiber slurry and aids in uniformity. The aramid nanofiber slurry was poured into the sheet mold. The slurry and DMSO were mixed with a propeller-equipped electric drill to a nearly uniform mixture. Negative pressure (about 10 Hg) was applied to the sheet mold for about 2 minutes to remove the DMSO. In some experiments, negative pressure was applied for 40-50 seconds. The sample was then washed with water. Although not limited by the mechanism, the water removes excess DMSO and strengthens the sample. The sample was then transferred to an oven and dried at 70 °C for about 2 hours. After drying, the sample can be easily peeled off. After drying, the sample was cut into 3 inch x 12 inch strips and given to a calendar to obtain the desired thickness. The nanoporous separator membrane samples were typically 12-16 gsm and 12-16 μm.
[0056] Example 3 HF binding to nanoporous separator membranes
[0057] The nanoporous separator membranes were incubated with either a control solution or a 1.2M LiPF6EC / EMC electrolyte solution containing 10.75 ppm HF. After incubation, the membranes were visually inspected. The membranes soaked with the 1.2M LiPF6EC / EMC electrolyte solution containing 10.75 ppm HF were pink or reddish in color, whereas the membranes soaked with the control solution remained yellowish. The results from such an experiment are shown in Figure 4. A sample of the nanoporous separator membrane was examined by XPS, and the spectrum obtained from such an experiment is shown in Figure 2. A sample of the 1.2M LiPF6EC / EMC soaked separator was examined by XPS, and the spectrum obtained from such an experiment is shown in Figure 3, Figure 3A, and Figure 3B. The analysis spectrum in Figure 3A shows the addition of about 4 atomic % fluorine (F) to the sample compared to that of the plain aramid nanofiber ICM. A zoom in on the carbon region in FIG. 3B also reveals that the added fluorine is bonded to the carbon by the appearance of a C—F bond peak.
[0058] Example 4 Observation of nanoporous separator membrane by scanning electron microscope
[0059] The specimen was cut and mounted on an SEM specimen holder using double-sided carbon tape and sputter coated with gold. Figure 1A was taken at 25,000x magnification, and Figure 1B was taken at 2500x magnification.
[0060] Example 5 Preparation of Moisture Absorbing Film
[0061] Moisture-wicking membranes containing aramid microfibers and aramid nanofibers were prepared by blending Kevlar pulp with DMSO and various Group I or Group II bases including potassium hydroxide, sodium hydroxide, lithium hydroxide, barium hydroxide, or calcium hydroxide. The mixture was blended under high shear to form a slurry containing aramid microfibers and aramid nanofibers. A mold was prepared with an aprotic solvent and the slurry was placed in the mold. The slurry was stirred in the mold and then subjected to negative pressure. After this negative pressure treatment, the samples were dried at 150-250°C for 2 hours. The tensile strength, stiffness, and air permeability of each membrane were evaluated. The results obtained from this series of experiments are shown in Figure 5 and summarized in Table 1 below (where air permeability is a function of porosity). The basic data measured at this point are as follows:
[0062] Properties of hygroscopic films prepared using various bases. [Table 1]
[0063] Example 6 Capacity Evaluation
[0064] Moisture-wicking membranes were prepared using various bases as described above. Lithium-ion batteries were prepared with moisture-wicking membranes as the ion-conducting membrane. A 1.2M LiPF6EC / EMC electrolyte solution was used for the batteries. The batteries were cycled multiple times. The percent capacity remaining was evaluated after 50, 100, 150, 200, 250, and 300 cycles. Results from such experiments are shown in FIG. 6. As described therein, batteries with membranes prepared with barium hydroxide and calcium hydroxide maintained greater than 90% capacity at 150, 200, 250, and 300 cycles. Batteries with membranes prepared with sodium hydroxide dropped to below 90% capacity at 200 cycles. Batteries with membranes prepared with potassium hydroxide showed mixed results, with at least one dropping to below 90% capacity at 150 cycles.
[0065] Example 7 Moisture absorption capacity Wetting membranes were prepared by incubating aramid microfibers with potassium hydroxide, sodium hydroxide, lithium hydroxide, barium hydroxide or calcium hydroxide. Samples of each membrane were prepared. The mass (g) of each membrane sample was measured. Each membrane sample was incubated in a 1:1 w / w solution of EC:DMC containing 1000 ppm water. The membrane sample was removed from the wetting solvent. The mass (g) of water absorbed was determined by measuring the amount of water remaining in the incubation solvent. Results from such experiments are shown in Table 2 and in graphical form in Figure 7. As shown there, the percent wetting capacity (g water / g membrane sample) is shown on the y-axis. The base used to prepare each wetting membrane is shown on the x-axis. In the particular experiment shown here, the membrane prepared with LiOH absorbed water equivalent to more than 5% of its mass, the membrane prepared with NaOH absorbed water equivalent to more than 10% of its mass, the membrane prepared with KOH absorbed water equivalent to more than 15% of its mass, the membrane prepared with Ba(OH)2 absorbed water equivalent to more than 20% of its mass, and the membrane prepared with Ca(OH)2 absorbed water equivalent to more than 45% of its mass. These results are based on measurements of many different considerations, including 1) the weight of the membrane after drying at 150°C for 1 hour, 2) the moisture concentration in the electrolyte (measured by Karl Fischer titration) measured after immersing the membrane in 300 ml of electrolyte for 48 hours, 3) the amount of moisture removed from the membrane calculated from the moisture concentration in 2) and the amount of electrolyte (300 ml) (where this amount is calculated as 300 ml * (moisture concentration - initial moisture concentration) / 1000, where the initial moisture concentration is the amount of moisture in the electrolyte before immersion (~2000 ppm)), and 4) the amount of moisture removed as a membrane weight ratio, essentially the measurement result of 3) / [1000 * weight of 1)]. The tabular results are as follows:
[0066] Properties of hygroscopic films prepared using various bases. [Table 2]
[0067] These results and examples demonstrate the significant potential for many beneficial properties within specific end applications utilizing such membranes containing polyaramid microfibers and polyaramid nanofibers. Moisture absorption and HF removal, as non-limiting examples, provide significant results not previously available, at least in the lithium ion battery industry.
Claims
1. A hydrogen fluoride removal separator membrane for a lithium ion battery containing lithium hexafluorophosphate as an electrolyte, the hydrogen fluoride removal separator membrane comprising aramid microfibers and aramid nanofibers.
2. 10. The hydrogen fluoride removal separator membrane of claim 1, wherein the membrane changes color upon binding of hydrogen fluoride to the membrane.
3. A moisture-absorbing film comprising aramid microfibers and aramid nanofibers for use in a lithium-ion battery containing lithium hexafluorophosphate as an electrolyte, the moisture-absorbing film being characterized in that the film is capable of absorbing moisture equivalent to at least 1% of its mass when exposed for 48 hours to 300 ml of an electrolyte solution containing EC and DMC in a 1:1 ratio and containing 1000 ppm water at a ratio of 0.1653-0.1764 g of the film.
4. The moisture wicking membrane of claim 3 further comprising at least one additive.
5. The additive is Al 2 O 3 The moisture-absorbing film according to claim 4, characterized in that
6. 4. The moisture wicking film of claim 3, wherein the film reduces dendritic growth.
7. 4. The moisture absorbing membrane of claim 3, wherein the membrane has a tensile strength of at least 35 MPa.
8. 4. The moisture absorbing membrane of claim 3, wherein said membrane exhibits an air permeability of greater than 65 Gurley seconds.
9. 4. The moisture absorbing membrane of claim 3, wherein the membrane has an ionic conductivity of greater than 0.01 mS / cm.
10. The moisture-absorbing film according to claim 3, characterized in that the average pore size of the film is 50 to 100 nm.
11. 4. The moisture absorbing membrane of claim 3, wherein the membrane is capable of absorbing moisture equivalent to at least 5% to at least 45% of the membrane mass.
12. A battery comprising the moisture-absorbing film according to claim 3.
13. The battery of claim 12, wherein the battery having a moisture-absorbing membrane exhibits hydrogen fluoride removal properties.
14. 13. The battery of claim 12, wherein a component of the battery has a surface adjacent to a surface of the moisture wicking membrane.
15. 15. The battery of claim 14, wherein the component is selected from the group of components including an anode, a cathode, and an encapsulant material.
16. 14. The battery of claim 13, wherein the battery comprises an ion-conducting membrane that includes the moisture-absorbing membrane.
17. 14. The battery of claim 13, wherein the battery exhibits at least 90% capacity after 250 cycles.
18. A battery comprising the hydrogen fluoride removal separator membrane according to claim 1.
19. 1. A method for preparing a hydrogen fluoride removal separator membrane for a lithium ion battery containing lithium hexafluorophosphate in an electrolyte, the method comprising the steps of: (a) preparing a blend of aramid pulp, dimethyl sulfoxide, and potassium hydroxide; (b) exposing the blend to high shear forces to form a slurry; (c) preparing a mold with a layer of DMSO; (d) adding the slurry to the mold; (e) stirring the slurry and DMSO; (f) applying a negative pressure; (g) removing residual DMSO; and (h) drying the slurry to form a nanoporous separator membrane comprising aramid microfibers and aramid nanofibers.
20. 20. The method of claim 19, wherein the ratio of aramid microfibers to aramid nanofibers is in the range of 90:10 to 10:
90.
21. 20. The method of claim 19, wherein the aramid microfibers and the aramid nanofibers comprise 0.1-2% of the slurry.
22. 20. The method of claim 19, wherein the method produces a nanoporous separator membrane in less than 24 hours.
23. 20. The method of claim 19, wherein exposing the formulation to the high shear force occurs for less than 2 hours.
24. 20. The method of claim 19, wherein at least 10% and up to 95% of the DMSO is removed from the slurry by the negative pressure.
25. 20. The method of claim 19, wherein the negative pressure is applied for less than five minutes.
26. 20. The method of claim 19, wherein residual DMSO is removed with water.
27. 20. The method of claim 19, characterized in that the drying occurs at 50°C to 100°C.
28. 20. The method of claim 19, characterized in that the drying occurs at 60°C to 90°C.
29. 20. The method of claim 19, wherein the mold is selected from the group of molds consisting of sheet molds, casting molds, mold and deckle, and cylinder molds.
30. 1. A method for preparing a hygroscopic film comprising aramid microfibers and aramid nanofibers for use in a lithium ion battery containing lithium hexafluorophosphate as an electrolyte, comprising the steps of: (a) preparing a blend of aramid pulp, an aprotic solvent, and a base; (b) exposing the blend to high shear to form a slurry comprising aramid microfibers and aramid nanofibers; (c) preparing a mold with a layer of aprotic solvent; (d) adding the slurry to the mold; (e) stirring the slurry in the presence of the aprotic solvent; (f) applying a negative pressure; and (g) drying to form a hygroscopic film comprising aramid microfibers and aramid nanofibers.
31. 31. The method of claim 30, wherein the base is selected from the group consisting of group I bases and group II bases.
32. 32. The method of claim 31, wherein the Group II base is selected from the group consisting of barium hydroxide and calcium hydroxide.
33. 33. The method of claim 32, characterized in that the hygroscopic membrane is prepared in less than 96 hours.
34. 31. The method of claim 30, wherein the aprotic solvent is DMSO.
35. 31. The method of claim 30, characterized in that the drying occurs at from 50°C to 200°C.
36. 31. The method of claim 30, characterized in that the drying occurs at 180°C or higher.
37. 4. A method for reducing moisture in a battery, comprising incorporating within said battery the moisture wicking membrane of claim 3.
38. 13. A method for reducing free HF in a battery, comprising incorporating within said battery the hydrogen fluoride removal separator membrane of claim 1.
39. 13. A visual indicator of HF exposure comprising the hydrogen fluoride removal separator membrane of claim 1 and an observation opening within which the hydrogen fluoride removal separator membrane is disposed, the visual indicator changing color upon binding of HF to the hydrogen fluoride removal separator membrane.
40. 40. A battery system comprising the visual indicator of claim 39.
Citation Information
Patent Citations
Diaphragm for lithium battery and preparation method thereof
CN110364665A
Method for fabricating single-layer lithium-ion battery separators with nanofiber and microfiber components
JP2016506017A
Dendrite Inhibition Ions from Aramid Nanofibers Resistant to Extreme Battery Conditions
JP2017510030A
Gels and nanocomposites containing ANFS
JP2019511387A